Highly compatible sponge for household products and method for manufacturing the same

JP2026534519APending Publication Date: 2026-10-16ZHENGQI NEW MATERIALS TECHNOLOGY (CHANGZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026519346
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-07-12
Filing Date
2025-08-25
Publication Date
2026-10-16

Smart Images

  • Figure 2026534519000001
    Figure 2026534519000001
  • Figure 2026534519000002
    Figure 2026534519000002
  • Figure 2026534519000003
    Figure 2026534519000003
Patent Text Reader

Abstract

The present invention relates to the field of sponge materials, and more particularly to a highly compatible sponge for household goods and a method for producing the same. The present invention includes the steps of: uniformly mixing a polyether polyol, halloysite nanotubes, and natural crystal powder to obtain a first component; mixing additives to obtain a second component; uniformly mixing the first and second components, adding toluene diisocyanate to the mixed sample, and stirring until foaming occurs; heating the foamed organic material to mature it to obtain a urethane sponge; finishing the urethane sponge to obtain a highly compatible sponge for household goods. The sponge produced by the present invention is used in household goods, has high compatibility, and possesses excellent and sustained flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to the technical field of sponge materials, and in particular to a highly compatible sponge for household products and a method for producing the same. BACKGROUND ART

[0002] Urethane sponge is a foam material made from urethane raw materials, and has characteristics such as light weight, flexibility, shock absorption, and insulation. It is widely applied in the field of household products, particularly in furniture manufacturing. Urethane sponge has an extremely wide range of applications in furniture manufacturing, and is mainly used in the production of furniture products such as sofas, seats, and mattresses. With its excellent elasticity and comfort, urethane sponge can provide good support and pressure distribution, enabling users to obtain a more comfortable and relaxed experience when using these pieces of furniture. For example, in sofas and seats, urethane sponge not only increases the softness of the cushion, but also can effectively absorb shocks and reduce the sense of vibration to the human body. In addition, urethane sponge also has a relatively long service life and a strong protective effect, which makes it widely popularized and applied in furniture manufacturing. In mattress production, urethane sponge can provide a better sleep experience due to its excellent shock absorption performance. In other words, urethane sponge, with its properties such as light weight, flexibility, shock absorption, and insulation, is widely applied in the field of household products, particularly in furniture manufacturing. Its excellent elasticity and comfort make it an ideal choice for furniture manufacturing, bringing users a better use experience.

[0003] Chinese patent application publication number CN106279608 discloses a mugwort-containing polyurethane composite household foam sponge, manufactured from parts by weight of microcrystalline cellulose, soybean oil, diethylene glycol, potassium hydroxide, polyether polyol, foaming agent, foam stabilizer, catalyst, toluene diisocyanate, distilled water, ethyl orthosilicate, mugwort, and silicone oil. The foam sponge cushion manufactured according to this invention has properties such as good comfort, environmental protection, excellent rebound modulus, and high tensile strength, but it does not have flame retardant properties as a furniture item, posing a safety risk. Chinese patent application publication number CN109651643 discloses a flame-retardant polyurethane sponge, its manufacturing method, and applications. The method includes the steps of: immersing a urethane sponge in an aqueous dispersion of halloysite nanotubes, vigorously pressing the urethane sponge, and uniformly coating the urethane sponge with halloysite nanotubes by stirring or ultrasonic waves; placing the urethane sponge in a drying device and inverting the sponge once at regular intervals; and, after the liquid has gradually evaporated, removing the halloysite nanotubes that are not firmly bonded to obtain a flame-retardant urethane sponge coated and modified with halloysite nanotubes. This sponge has a certain degree of flame retardancy, but the flame retardant components tend to fall off the sponge surface, and it does not have long-term flame retardancy. [Overview of the project] [Problems that the invention aims to solve]

[0004] To overcome the above-mentioned conventional technical problems, the present invention provides a highly compatible sponge for household goods and a method for manufacturing the same. The sponge manufactured according to the present invention is used in household goods, has high compatibility, and possesses excellent and sustained flame retardant properties. [Means for solving the problem]

[0005] To achieve the above-mentioned objectives of the invention, the present invention employs the following technical approach.

[0006] A method for manufacturing highly compatible sponges for household products is: S1, a step of uniformly mixing polyether polyol, halloysite nanotubes, and natural crystal powder to obtain the first component, The process involves uniformly mixing S2, dibutyltin diacetate, and triethylamine to obtain a composite catalyst, then adding foaming agent water and foam stabilizer silicone oil to the composite catalyst to obtain the second component. Step S3 involves uniformly mixing the first and second components to obtain a mixed sample, adding toluene diisocyanate to the mixed sample, and stirring until foaming occurs. Step S4 involves heating and maturing the foamed organic matter to obtain a urethane sponge. Step S5: Add dopamine hydrochloride to Tris buffer, stir to mix uniformly, obtain a mixed solution, add modified halloysite nanotubes to the mixed solution, stir to mix uniformly, adjust the pH to 8-9, and obtain a dopamine reaction solution. S6 includes the step of immersing the urethane sponge obtained in step S4 in a dopamine reaction solution, heating it to react, and after the reaction is complete, removing the urethane sponge and drying it to obtain a highly suitable sponge for household products.

[0007] This invention involves mixing natural crystal powder into a sponge. The infrared radiation emitted from the natural crystal powder creates a unique and stable frequency that strengthens the immune system, promotes the rapid elimination of toxins from the body, and increases oxygen levels. Because this special frequency is the same vibrational frequency as that of humans, it has the function of reducing muscle tension, lowering heart rate, relaxing breathing, increasing oxygen levels in the body, relieving stress, and improving sleep.

[0008] This invention produces a urethane sponge using polyether polyol and toluene diisocyanate as reaction monomers, through the action of a foaming agent and a foam stabilizer. This invention imparts flame retardancy to the urethane sponge by bonding it with halloysite nanotubes, utilizing the flame retardancy of halloysite nanotubes. Specifically, the flame retardancy of the urethane sponge is achieved in two ways. In one way, halloysite nanotubes are mixed into the urethane sponge by adding them during the reaction process between the polyether polyol and toluene diisocyanate. In another way, a layer of halloysite nanotubes is bonded to the surface of the urethane. Due to the synergistic effect of both, the urethane sponge has relatively excellent flame retardancy.

[0009] In the process of bonding halloysite nanotubes to the urethane surface, the halloysite nanotubes tend to detach from the sponge surface using conventional immersion methods. Therefore, this invention utilizes the autopolymerization reaction of dopamine to attach the halloysite nanotubes to the urethane sponge surface, thereby improving the bonding force between the halloysite nanotubes and the urethane sponge surface and improving the problem of the halloysite nanotubes easily detaching from the sponge surface.

[0010] Preferably, the natural crystal powder in step S1 is It is a mixture of fluorite powder, orange calcite powder, shungite powder, bloodstone powder, selenite powder, aragonite powder, tourmaline powder, white quartz powder, amethyst powder, rose quartz powder, aventurine powder, citrine powder, red jasper powder, serpentine powder, and sodalite powder.

[0011] Preferably, the mass ratio of dibutyltin diacetate to triethylamine in step S2 is 1:(2~3).

[0012] Preferably, the amount of toluene diisocyanate added in step S3 is 40-60 wt% of the polyether polyol in step S1.

[0013] Preferably, the heating and aging temperature in S4 is controlled to 60-70°C.

[0014] Preferably, the method for producing the modified halloysite nanotubes in step S5 is: The process involves adding the silane coupling agent KH560 to a mixed solution of ethanol and water (ethanol to water volume ratio 10:1), adding halloysite nanotubes, heating to 50°C, stirring, reacting at a constant temperature for 2 hours, followed by centrifugation, washing, and drying to obtain coupling agent-modified halloysite nanotubes. The method includes the steps of: adding superbranched polyvinylimidazole to water and stirring to dissolve it, preparing a superbranched polyvinylimidazole solution with a mass concentration of 0.5%; adding the coupling agent-modified halloysite nanotubes obtained above to the superbranched polyvinylimidazole solution, heating the reaction, and then centrifugation, washing, and drying to obtain modified halloysite nanotubes.

[0015] Another problem in the process of bonding halloysite nanotubes to the urethane surface is that the halloysite nanotubes are randomly dispersed in the Tris buffer, and the halloysite nanotubes dispersed near the surface of the urethane sponge are insufficient to bind with polydopamine and form a halloysite nanotube flame-retardant protective layer. Therefore, the present invention performs a surface modification treatment on the halloysite nanotubes, first grafting epoxy groups onto the surface of the halloysite nanotubes, then reacting the epoxy groups with the amino groups on the superbranched polyvinylimidazole to graft the superbranched polyvinylimidazole onto the halloysite nanotubes, thereby supporting a large number of amino groups on the surface of the halloysite nanotubes, and by forming hydrogen bonding interaction forces between the amino groups on the surface of the halloysite nanotubes and the amino groups on the polydopamine on the surface of the urethane sponge, more halloysite nanotubes are bonded to the surface of the urethane sponge, further forming a halloysite nanotube flame-retardant protective layer.

[0016] Preferably, glutaraldehyde is further added to the mixed solution in step S5.

[0017] As described above, the present invention utilizes the autopolymerization reaction of dopamine to attach halloysite nanotubes to the surface of a urethane sponge, thereby improving the bonding force between the halloysite nanotubes and the urethane sponge surface and improving the problem of halloysite nanotubes easily detaching from the sponge surface. However, the above method only improves the problem of halloysite nanotubes easily detaching from the sponge surface to some extent and does not completely solve the problem of halloysite nanotubes detaching from the sponge surface. Therefore, in order to further improve the bonding force between halloysite nanotubes and the sponge surface, the present invention adds glutaraldehyde to the Tris buffer solution and uses glutaraldehyde to crosslink the amino groups on the polydopamine with the amino groups on the surface of the halloysite nanotubes, thereby firmly bonding the halloysite nanotubes to the urethane sponge surface and completely solving the problem of halloysite nanotubes detaching from the sponge surface.

[0018] Preferably, sodium alginate is further added to the second component in step S2.

[0019] In the proposed method of this invention, as described above, the amino groups on the surface of the halloysite nanotubes and the amino groups on the polydopamine on the surface of the urethane sponge form hydrogen bonding interactions, thereby bonding more halloysite nanotubes to the surface of the urethane sponge and further forming a halloysite nanotube flame-retardant protective layer. However, the density of the halloysite nanotube flame-retardant protective layer is uneven; that is, a dense halloysite nanotube flame-retardant protective layer is formed in some areas of the sponge surface, while other areas remain exposed, which has a certain effect on the flame-retardant performance of the urethane sponge. To solve this problem, the present invention adds sodium alginate during the manufacturing process of the urethane sponge, uniformly disperses the sodium alginate in the urethane sponge, and adds COO to the urethane sponge. -are supported, and the amino groups on the nano-surface of halloysite are positively charged. Through electrostatic interaction forces, halloysite nanotubes are uniformly bonded to the surface of the urethane sponge, thereby forming a uniform dense flame-retardant protective layer of halloysite nanotubes on the surface of the urethane sponge, which further improves the flame retardant performance of the urethane sponge.

[0020] Preferably, the added amount of the sodium alginate is 0.3 to 0.6 wt% based on the mass of the polyether polyol.

[0021] The highly compatible sponge for household goods is produced by the method described above.

Effects of the Invention

[0022] The present invention has the following beneficial effects.

[0023] 1) Natural crystal powder is mixed into the sponge. The infrared rays emitted from the natural crystal powder generate a unique and stable frequency, which strengthens the immune system, promotes the rapid excretion of body toxins, and increases the oxygen level. Since such a special frequency is the same as the vibration frequency of human beings, it has the functions of reducing muscle tension, lowering heart rate, relaxing breathing, increasing the oxygen content in the body, relieving stress, and improving sleep.

[0024] 2) By adding halloysite nanotubes during the reaction process of polyether polyol and toluene diisocyanate, the halloysite nanotubes are mixed inside the urethane sponge, while a layer of halloysite nanotubes is bonded to the urethane surface. Through the synergistic effect of both, the urethane sponge has relatively excellent flame retardant performance.

[0025] 3) Halloysite nanotubes are subjected to a surface modification treatment to support a large number of amino groups on the surfaces of the halloysite nanotubes, and the amino groups on the surfaces of the halloysite nanotubes form hydrogen bonding interaction forces with the amino groups on polydopamine on the surface of the urethane sponge, so that more halloysite nanotubes are bonded to the surface of the urethane sponge, and a flame-retardant protective layer of halloysite nanotubes is further formed.

[0026] 4) Glutaraldehyde is used to crosslink the amino groups on polydopamine and the amino groups on the surfaces of halloysite nanotubes, so that the halloysite nanotubes are firmly bonded to the surface of the urethane sponge, completely solving the problem that the halloysite nanotubes fall off from the sponge surface.

[0027] 5) Sodium alginate is added during the production process of the urethane sponge, and halloysite nanotubes are uniformly bonded to the surface of the urethane sponge by electrostatic interaction forces, so that a uniform flame-retardant dense protective layer of halloysite nanotubes is formed on the surface of the urethane sponge, further improving the flame-retardant performance of the urethane sponge. [Modes for Carrying Out the Invention]

[0028] Hereinafter, the present invention will be described in further clear and detailed detail with reference to specific examples. Those skilled in the art can implement the present invention based on these descriptions. It should be noted that the examples of the present invention described in the following description are generally only a part of the examples of the present invention, not all of the examples. Therefore, all other examples obtained by a person of ordinary skill in the art without creative work based on the examples of the present invention shall fall within the protection scope of the present invention.

[0029] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available or available to those skilled in the art, and unless otherwise specified, all methods used in the examples of the present invention are methods mastered by those skilled in the art.

[0030] Example 1 Manufacturing of modified halloysite nanotubes: Silane coupling agent KH560 was added to a mixed solution of ethanol and water (ethanol to water volume ratio 10:1) at a mass-to-volume ratio of 1g / 300mL. Then, halloysite nanotubes were added, and the mass ratio of halloysite nanotubes to silane coupling agent KH560 was 1:0.2. The mixture was heated to 50°C, stirred, and reacted at a constant temperature for 2 hours. After centrifugation, washing, and drying, coupling agent-modified halloysite nanotubes were obtained. Superbranched polyvinylimidazole was added to water and dissolved by stirring to prepare a 0.5% by mass superbranched polyvinylimidazole solution. The coupling agent-modified halloysite nanotubes obtained above were added to the superbranched polyvinylimidazole solution, heated to 80°C, and allowed to react for 5 hours. After centrifugation, washing, and drying, modified halloysite nanotubes were obtained.

[0031] A method for manufacturing a highly compatible sponge for household products, S1 is a step in which a polyether polyol 330N with a molecular weight of 5000, halloysite nanotubes, and natural crystal powder are uniformly mixed, the mass ratio of the polyether polyol to the halloysite nanotubes being 1:0.04 and the mass ratio of the polyether polyol to the natural crystal powder being 1:0.06, and a first component is obtained. The aforementioned natural crystal powder is The step involves mixing equal masses of the following substances: fluorite powder, orange calcite powder, shungite powder, bloodstone powder, selenite powder, aragonite powder, tourmaline powder, white quartz powder, amethyst powder, rose quartz powder, aventurine powder, citrine powder, red jasper powder, serpentine powder, and sodalite powder. Step 2 involves uniformly mixing S2, dibutyltin diacetate and triethylamine (in a mass ratio of dibutyltin diacetate to triethylamine of 1:3) to obtain a composite catalyst, the mass of which is 0.3% of the mass of the polyether polyol, then adding to the composite catalyst 10 times the mass of the composite catalyst, foaming agent water, 5 times the mass of the composite catalyst, foam stabilizer silicone oil, and sodium alginate, the amount of added sodium alginate being 0.5% of the mass of the polyether polyol, to obtain the second component. Step S3 involves uniformly mixing the first and second components to obtain a mixed sample, adding toluene diisocyanate to the mixed sample so that the amount of toluene diisocyanate added is 55 wt% of the polyether polyol, stirring until foaming occurs, and continuing stirring for 30 seconds after foaming. Step S4 involves heating the foamed organic material to 70°C and allowing it to mature, controlling the maturation time to 5 hours, in order to obtain a urethane sponge. Step S5: Add dopamine hydrochloride and glutaraldehyde to Tris buffer so that the mass ratio of dopamine hydrochloride to Tris buffer is 1:2 and the amount of glutaraldehyde added is 1.0 wt% of the dopamine hydrochloride. Stir to mix uniformly to obtain a mixed solution. Add modified halloysite nanotubes to the mixed solution so that the mass ratio of modified halloysite nanotubes to dopamine hydrochloride is 1:3. Stir to mix uniformly, adjust the pH to 9 to obtain a dopamine reaction solution. S6 includes the step of immersing the urethane sponge obtained in step S4 in a dopamine reaction solution, heating it to 60°C, allowing the reaction to proceed for 10 hours, removing the urethane sponge after the reaction is complete, and drying it in an oven at 50°C for 8 hours to obtain a highly suitable sponge for household use.

[0032] Example 2 Manufacturing of modified halloysite nanotubes: Silane coupling agent KH560 was added to a mixed solution of ethanol and water (ethanol to water volume ratio 10:1) at a mass-to-volume ratio of 1g / 300mL. Then, halloysite nanotubes were added, and the mass ratio of halloysite nanotubes to silane coupling agent KH560 was 1:0.2. The mixture was heated to 50°C, stirred, and reacted at a constant temperature for 2 hours. After centrifugation, washing, and drying, coupling agent-modified halloysite nanotubes were obtained. Superbranched polyvinylimidazole was added to water and dissolved by stirring to prepare a 0.5% by mass superbranched polyvinylimidazole solution. The coupling agent-modified halloysite nanotubes obtained above were added to the superbranched polyvinylimidazole solution, heated to 80°C, and allowed to react for 5 hours. After centrifugation, washing, and drying, modified halloysite nanotubes were obtained.

[0033] A method for manufacturing a highly compatible sponge for household products, S1 is a step in which a polyether polyol 330N with a molecular weight of 5000, halloysite nanotubes, and natural crystal powder are uniformly mixed, the mass ratio of the polyether polyol to the halloysite nanotubes being 1:0.03 and the mass ratio of the polyether polyol to the natural crystal powder being 1:0.06, and a first component is obtained. The aforementioned natural crystal powder is The step involves mixing equal masses of the following substances: fluorite powder, orange calcite powder, shungite powder, bloodstone powder, selenite powder, aragonite powder, tourmaline powder, white quartz powder, amethyst powder, rose quartz powder, aventurine powder, citrine powder, red jasper powder, serpentine powder, and sodalite powder. Step 2 involves uniformly mixing S2, dibutyltin diacetate and triethylamine (in a mass ratio of dibutyltin diacetate to triethylamine of 1:2) to obtain a composite catalyst, the mass of which is 0.3% of the mass of the polyether polyol, then adding to the composite catalyst 10 times the mass of the composite catalyst, foaming agent water, 5 times the mass of the composite catalyst, foam stabilizer silicone oil, and sodium alginate, the amount of added sodium alginate being 0.4% of the mass of the polyether polyol, to obtain the second component. Step S3 involves uniformly mixing the first and second components to obtain a mixed sample, adding toluene diisocyanate to the mixed sample so that the amount of toluene diisocyanate added is 45 wt% of the polyether polyol, stirring until foaming occurs, and continuing stirring for 30 seconds after foaming. Step S4 involves heating the foamed organic material to 60°C and allowing it to mature, controlling the maturation time to 5 hours, in order to obtain a urethane sponge. Step S5: Add dopamine hydrochloride and glutaraldehyde to Tris buffer so that the mass ratio of dopamine hydrochloride to Tris buffer is 1:2 and the amount of glutaraldehyde added is 1.0 wt% of the dopamine hydrochloride. Stir to mix uniformly to obtain a mixed solution. Add modified halloysite nanotubes to the mixed solution so that the mass ratio of modified halloysite nanotubes to dopamine hydrochloride is 1:3. Stir to mix uniformly, adjust the pH to 8 to obtain a dopamine reaction solution. S6 includes the step of immersing the urethane sponge obtained in step S4 in a dopamine reaction solution, heating it to 60°C, allowing the reaction to proceed for 10 hours, removing the urethane sponge after the reaction is complete, and drying it in an oven at 50°C for 8 hours to obtain a highly suitable sponge for household use.

[0034] Example 3 Manufacturing of modified halloysite nanotubes: Silane coupling agent KH560 was added to a mixed solution of ethanol and water (ethanol to water volume ratio 10:1) at a mass-to-volume ratio of 1g / 300mL. Then, halloysite nanotubes were added, and the mass ratio of halloysite nanotubes to silane coupling agent KH560 was 1:0.2. The mixture was heated to 50°C, stirred, and reacted at a constant temperature for 2 hours. After centrifugation, washing, and drying, coupling agent-modified halloysite nanotubes were obtained. Superbranched polyvinylimidazole was added to water and dissolved by stirring to prepare a 0.5% by mass superbranched polyvinylimidazole solution. The coupling agent-modified halloysite nanotubes obtained above were added to the superbranched polyvinylimidazole solution, heated to 80°C, and allowed to react for 5 hours. After centrifugation, washing, and drying, modified halloysite nanotubes were obtained.

[0035] A method for manufacturing a highly compatible sponge for household products, S1 is a step in which a polyether polyol 330N with a molecular weight of 5000, halloysite nanotubes, and natural crystal powder are uniformly mixed, the mass ratio of the polyether polyol to the halloysite nanotubes being 1:0.03 and the mass ratio of the polyether polyol to the natural crystal powder being 1:0.06, and a first component is obtained. The aforementioned natural crystal powder is The step involves mixing equal masses of the following substances: fluorite powder, orange calcite powder, shungite powder, bloodstone powder, selenite powder, aragonite powder, tourmaline powder, white quartz powder, amethyst powder, rose quartz powder, aventurine powder, citrine powder, red jasper powder, serpentine powder, and sodalite powder. Step 2 involves uniformly mixing S2, dibutyltin diacetate and triethylamine (in a mass ratio of dibutyltin diacetate to triethylamine of 1:2.5) to obtain a composite catalyst, the mass of which is 0.3% of the mass of the polyether polyol, then adding to the composite catalyst 10 times the mass of the composite catalyst, foaming agent water, 5 times the mass of the composite catalyst, foam stabilizer silicone oil, and sodium alginate, the amount of added sodium alginate being 0.45% of the mass of the polyether polyol, to obtain the second component. Step S3 involves uniformly mixing the first and second components to obtain a mixed sample, adding toluene diisocyanate to the mixed sample so that the amount of toluene diisocyanate added is 50 wt% of the polyether polyol, stirring until foaming occurs, and continuing stirring for 30 seconds after foaming. Step S4 involves heating the foamed organic material to 65°C and allowing it to mature, controlling the maturation time to 5 hours, in order to obtain a urethane sponge. Step S5: Add dopamine hydrochloride and glutaraldehyde to Tris buffer so that the mass ratio of dopamine hydrochloride to Tris buffer is 1:2 and the amount of glutaraldehyde added is 1.0 wt% of the dopamine hydrochloride. Stir to mix uniformly to obtain a mixed solution. Add modified halloysite nanotubes to the mixed solution so that the mass ratio of modified halloysite nanotubes to dopamine hydrochloride is 1:3. Stir to mix uniformly, adjust the pH to 8.5 to obtain a dopamine reaction solution. S6 includes the step of immersing the urethane sponge obtained in step S4 in a dopamine reaction solution, heating it to 60°C, allowing the reaction to proceed for 10 hours, removing the urethane sponge after the reaction is complete, and drying it in an oven at 50°C for 8 hours to obtain a highly suitable sponge for household use.

[0036] Example 4 Manufacturing of modified halloysite nanotubes: Silane coupling agent KH560 was added to a mixed solution of ethanol and water (ethanol to water volume ratio 10:1) at a mass-to-volume ratio of 1g / 300mL. Then, halloysite nanotubes were added, and the mass ratio of halloysite nanotubes to silane coupling agent KH560 was 1:0.2. The mixture was heated to 50°C, stirred, and reacted at a constant temperature for 2 hours. After centrifugation, washing, and drying, coupling agent-modified halloysite nanotubes were obtained. Superbranched polyvinylimidazole was added to water and dissolved by stirring to prepare a 0.5% by mass superbranched polyvinylimidazole solution. The coupling agent-modified halloysite nanotubes obtained above were added to the superbranched polyvinylimidazole solution, heated to 80°C, and allowed to react for 5 hours. After centrifugation, washing, and drying, modified halloysite nanotubes were obtained.

[0037] A method for manufacturing a highly compatible sponge for household products, S1 is a step in which a polyether polyol 330N with a molecular weight of 5000, halloysite nanotubes, and natural crystal powder are uniformly mixed, the mass ratio of the polyether polyol to the halloysite nanotubes being 1:0.05 and the mass ratio of the polyether polyol to the natural crystal powder being 1:0.06, and a first component is obtained. The aforementioned natural crystal powder is The step involves mixing equal masses of the following substances: fluorite powder, orange calcite powder, shungite powder, bloodstone powder, selenite powder, aragonite powder, tourmaline powder, white quartz powder, amethyst powder, rose quartz powder, aventurine powder, citrine powder, red jasper powder, serpentine powder, and sodalite powder. Step 2 involves uniformly mixing S2, dibutyltin diacetate and triethylamine (in a mass ratio of dibutyltin diacetate to triethylamine of 1:3) to obtain a composite catalyst, the mass of which is 0.3% of the mass of the polyether polyol, then adding 10 times the mass of the composite catalyst in foaming agent water, 5 times the mass of the composite catalyst in foam stabilizer silicone oil and sodium alginate, the amount of added sodium alginate being 0.6% of the mass of the polyether polyol, to obtain the second component. Step S3 involves uniformly mixing the first and second components to obtain a mixed sample, adding toluene diisocyanate to the mixed sample so that the amount of toluene diisocyanate added is 60 wt% of the polyether polyol, stirring until foaming occurs, and continuing stirring for 30 seconds after foaming. Step S4 involves heating the foamed organic material to 70°C and allowing it to mature, controlling the maturation time to 5 hours, in order to obtain a urethane sponge. Step S5: Add dopamine hydrochloride and glutaraldehyde to Tris buffer so that the mass ratio of dopamine hydrochloride to Tris buffer is 1:2 and the amount of glutaraldehyde added is 1.0 wt% of the dopamine hydrochloride. Stir to mix uniformly to obtain a mixed solution. Add modified halloysite nanotubes to the mixed solution so that the mass ratio of modified halloysite nanotubes to dopamine hydrochloride is 1:3. Stir to mix uniformly, adjust the pH to 9 to obtain a dopamine reaction solution. S6 includes the step of immersing the urethane sponge obtained in step S4 in a dopamine reaction solution, heating it to 60°C, allowing the reaction to proceed for 10 hours, removing the urethane sponge after the reaction is complete, and drying it in an oven at 50°C for 8 hours to obtain a highly suitable sponge for household use.

[0038] Example 5 Manufacturing of modified halloysite nanotubes: Silane coupling agent KH560 was added to a mixed solution of ethanol and water (ethanol to water volume ratio 10:1) at a mass-to-volume ratio of 1g / 300mL. Then, halloysite nanotubes were added, and the mass ratio of halloysite nanotubes to silane coupling agent KH560 was 1:0.2. The mixture was heated to 50°C, stirred, and reacted at a constant temperature for 2 hours. After centrifugation, washing, and drying, coupling agent-modified halloysite nanotubes were obtained. Superbranched polyvinylimidazole was added to water and dissolved by stirring to prepare a 0.5% by mass superbranched polyvinylimidazole solution. The coupling agent-modified halloysite nanotubes obtained above were added to the superbranched polyvinylimidazole solution, heated to 80°C, and allowed to react for 5 hours. After centrifugation, washing, and drying, modified halloysite nanotubes were obtained.

[0039] A method for manufacturing a highly compatible sponge for household products, S1 is a step in which a polyether polyol 330N with a molecular weight of 5000, halloysite nanotubes, and natural crystal powder are uniformly mixed, the mass ratio of the polyether polyol to the halloysite nanotubes being 1:0.02 and the mass ratio of the polyether polyol to the natural crystal powder being 1:0.06, and a first component is obtained. The aforementioned natural crystal powder is The step involves mixing equal masses of the following substances: fluorite powder, orange calcite powder, shungite powder, bloodstone powder, selenite powder, aragonite powder, tourmaline powder, white quartz powder, amethyst powder, rose quartz powder, aventurine powder, citrine powder, red jasper powder, serpentine powder, and sodalite powder. Step 1 involves uniformly mixing S2, dibutyltin diacetate and triethylamine (in a mass ratio of dibutyltin diacetate to triethylamine of 1:2) to obtain a composite catalyst, the mass of which is 0.3% of the mass of the polyether polyol, then adding to the composite catalyst 10 times the mass of the composite catalyst, foaming agent water, 5 times the mass of the composite catalyst, foam stabilizer silicone oil, and sodium alginate, the amount of added sodium alginate being 0.3% of the mass of the polyether polyol, to obtain the second component. Step S3 involves uniformly mixing the first and second components to obtain a mixed sample, adding toluene diisocyanate to the mixed sample so that the amount of toluene diisocyanate added is 40 wt% of the polyether polyol, stirring until foaming occurs, and continuing stirring for 30 seconds after foaming. Step S4 involves heating the foamed organic material to 60°C and allowing it to mature, controlling the maturation time to 5 hours, in order to obtain a urethane sponge. Step S5: Add dopamine hydrochloride and glutaraldehyde to Tris buffer so that the mass ratio of dopamine hydrochloride to Tris buffer is 1:2 and the amount of glutaraldehyde added is 1.0 wt% of the dopamine hydrochloride. Stir to mix uniformly to obtain a mixed solution. Add modified halloysite nanotubes to the mixed solution so that the mass ratio of modified halloysite nanotubes to dopamine hydrochloride is 1:3. Stir to mix uniformly, adjust the pH to 8 to obtain a dopamine reaction solution. S6 includes the step of immersing the urethane sponge obtained in step S4 in a dopamine reaction solution, heating it to 60°C, allowing the reaction to proceed for 10 hours, removing the urethane sponge after the reaction is complete, and drying it in an oven at 50°C for 8 hours to obtain a highly suitable sponge for household use.

[0040] Comparative Example 1 The differences between Comparative Example 1 and Example 1 are: The key difference is that dopamine hydrochloride is not added in step S5. The other operating steps are the same as in Example 1.

[0041] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is: The key is replacing modified halloysite nanotubes with ordinary halloysite nanotubes. The other operating steps are the same as in Example 1.

[0042] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is: The key point is that glutaraldehyde is not added in step S5. The other operating steps are the same as in Example 1.

[0043] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is: The key difference is that sodium alginate is not added in step S2. The other operating steps are the same as in Example 1.

[0044] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is: The key difference in step S1 is that natural crystal powder is not added. The other operating steps are the same as in Example 1.

[0045] Performance Test 1. Flame retardancy test: The flame retardancy of urethane sponge was tested based on GB / T8333-19872008 "Test Method for Combustibility of Expanded Polystyrene". The test results showed that the higher the oxygen index, the better the flame retardancy of the sponge, and conversely, the worse the flame retardancy of the sponge. The test results are shown in Table 1.

[0046] [Table 1]

[0047] 2. To test the bonding strength between the halloysite nanotubes, which are the flame-retardant material on the sponge surface, and the sponge itself, the sponges produced in Examples 1, 3, and 5 and Comparative Examples 1 and 3 were placed in an ultrasonic vibrator filled with water and vibrated at a frequency of 20 kHz for 5 hours. The sponges were then removed, dried in an oven at 50°C, and the flame-retardant performance of the urethane sponge was measured according to the test method of GB / T8333-19872008 "Test Method for Combustibility of Expanded Polystyrene". It was proven that the better the flame-retardant performance, the stronger the bonding strength between the halloysite nanotubes, which are the flame-retardant material on the sponge surface, and the sponge itself, and the better the durability of the sponge's flame-retardant performance. The test results are shown in Table 2.

[0048] [Table 2]

[0049] A comparison of Table 1 and Table 2 shows that the flame retardant performance of the urethane sponges produced in Examples 1-5 remained almost unchanged after ultrasonic vibration (before and after ultrasonic vibration). However, in Comparative Examples 1 and 3, the flame retardant performance of the urethane sponges significantly decreased after ultrasonic vibration. This demonstrates that the bond between the urethane sponge produced in the examples and the flame retardant substance, halloysite nanotubes, is stronger, resulting in more durable flame retardant performance compared to Comparative Examples 1 and 3.

[0050] 3. The tensile strength of the urethane sponge was tested based on GB / T6344-2008, "Measurement of tensile strength and tensile elongation at break of flexible foam polymer materials." The springback rate of the urethane sponge was tested based on GB / T6670-2008, "Measurement of springback performance of flexible foam polymer materials using the ball-dropping method," and the test results are shown in Table 3.

[0051] [Table 3]

[0052] 4. The far-infrared emission performance of the sponge was tested using the GB / T30127-2013 method, and the test results are shown in Table 4.

[0053] [Table 4]

[0054] The above are merely preferred embodiments of the present invention, and these preferred embodiments should not be considered limitations of the present invention. It should be noted that the scope of protection of the present invention should be limited to the scope of the claims. Those skilled in the art can make several improvements and retouches without departing from the spirit and scope of the present invention, and these improvements and retouches shall also be considered within the scope of protection of the present invention.

Claims

1. A method for manufacturing a highly compatible sponge for household products, Step S1, uniformly mixing polyether polyol, halloysite nanotubes, and natural crystal powder to obtain the first component, Step S2 involves uniformly mixing dibutyltin diacetate and triethylamine to obtain a composite catalyst, then adding foaming agent water and foam stabilizer silicone oil to the composite catalyst to obtain the second component. Step S3: Mix the first and second components uniformly to obtain a mixed sample, add toluene diisocyanate to the mixed sample, and stir until foaming occurs. Step S4: Heating and maturing the foamed organic matter to obtain a urethane sponge. Step S5: Add dopamine hydrochloride to Tris buffer, stir to mix uniformly, obtain a mixed solution, add modified halloysite nanotubes to the mixed solution, stir to mix uniformly, adjust the pH to 8-9, and obtain a dopamine reaction solution. A manufacturing method characterized by comprising the steps of S6, immersing the urethane sponge obtained in step S4 in a dopamine reaction solution, heating it to cause a reaction, removing the urethane sponge after the reaction is complete, drying it, and obtaining a highly suitable sponge for household products.

2. The natural crystal powder in step S1 is A method for producing a highly compatible sponge for household goods according to claim 1, characterized in that it is a mixture of the following substances: fluorite powder, orange calcite powder, shungite powder, bloodstone powder, selenite powder, aragonite powder, tourmaline powder, white quartz powder, amethyst powder, rose quartz powder, aventurine powder, citrine powder, red jasper powder, serpentine powder, and sodalite powder.

3. The method for producing a highly compatible sponge for household products according to claim 1, characterized in that the mass ratio of dibutyltin diacetate to triethylamine in step S2 is 1:(2-3).

4. The method for producing a highly compatible sponge for household products according to claim 1, characterized in that the amount of toluene diisocyanate added in step S3 is 40 to 60 wt% of the polyether polyol in step S1.

5. A method for producing a highly compatible sponge for household goods according to claim 1, characterized in that the heating and maturation temperature in S4 is controlled to 60 to 70°C.

6. The method for producing modified halloysite nanotubes in step S5 is as follows: The process involves adding the silane coupling agent KH560 to a mixed solution of ethanol and water (ethanol to water volume ratio 10:1), adding halloysite nanotubes, heating to 50°C, stirring, reacting at a constant temperature for 2 hours, followed by centrifugation, washing, and drying to obtain coupling agent-modified halloysite nanotubes. A method for producing a highly compatible sponge for household goods according to claim 1, comprising the steps of: adding superbranched polyvinylimidazole to water and stirring to dissolve it, preparing a superbranched polyvinylimidazole solution with a mass concentration of 0.5%; adding the coupling agent-modified halloysite nanotubes obtained above to the superbranched polyvinylimidazole solution, heating the reaction, and then centrifugation, washing, and drying to obtain modified halloysite nanotubes.

7. The method for producing a highly compatible sponge for household products according to claim 6, characterized in that glutaraldehyde is further added to the mixed solution in step S5.

8. The method for producing a highly compatible sponge for household products according to claim 7, characterized in that sodium alginate is further added to the second component in step S2.

9. The method for producing a highly compatible sponge for household products according to claim 7, characterized in that the amount of sodium alginate added is 0.3 to 0.6 wt% of the mass of the polyether polyol.

10. A highly compatible sponge for household products, characterized by being manufactured by the method described in any one of claims 1 to 9.